Теоретичні основи і технології очищення безкисневих газів від сірководню хінгідронним методом - Слюзар, Андрій Володимирович (Національний університет "Львівська політехніка", 2021)
У дисертації наведено результати досліджень, спрямованих на розвиток теоретичних основ і технологій очищення безкисневих (природних і технологічних) газів від H2S хінгідронними окисними системами (ХОС) з одержанням сірки. Досліджено взаємну розчинність інгредієнтів хінгідронного поглинального розчину (ХПР) та їх вплив на фізико-хімічні властивості розчину. Теоретично обґрунтовано вибір масообмінної апаратури для процесів хемосорбції H2S на стадії очищення газів та О2 на стадії регенерації поглинального розчину. Досліджено вплив умов формування ХОС на її окисно-відновні та фізико-хімічні властивості, що дало змогу вдосконалити технологію приготування поглинального розчину для очищення безкисневих газів від H2S. Вивчено фазову рівновагу в системі H2S - хінгідронний поглинальний розчин. Досліджено вплив різних факторів на хемосорбцію H2S з безкисневих газів і О2 з повітря ХПР у диспергуючих і барботажних абсорберах. Встановлено вплив вуглеводневих компонентів, які містяться у природних і технологічних газах, на хемосорбцію H2S та регенерацію ХПР. Досліджено процеси електрохімічної регенерації ХПР. Розроблено варіанти технологічних схем для очищення природних і технологічних газів від H2S з одержанням дрібнодисперсної сірки і можливістю комбінування цих технологій з технологією полімерної сірки, що підвищує економічну ефективність хінгідронного процесу знесірчення газів. В диссертации представлены результаты исследований, направленных на развитие теоретических основ и технологий очистки бескислородных (природных и технологических) газов от H2S хингидронными окислительными системами (ХОС) с получением серы. Исследованы взаимная растворимость ингредиентов хингидронного поглотительного раствора (ХПР) и их влияние физико-химические свойства раствора. Теоретически обоснован выбор массообменной аппаратуры для процессов хемосорбции H2S на стадии очистки газов и О2 на стадии регенерации поглотительного раствора. Исследовано влияние условий формирования ХОС на их окислительно-восстановительные и физико-химические свойства, что позволило усовершенствовать технологию приготовления ХПР для очистки бескислородных газов от H2S. Изучено фазовое равновесие в системе H2S – ХПР. Исследовано влияние различных факторов на хемосорбцию H2S из бескислородных газов и О2 из воздуха ХПР в диспергирующих и барботажных абсорберах. Установлено влияние углеводородных компонентов, содержащихся в природных и технологических газах, на хемосорбцию H2S и регенерацию ХПР. Исследованы процессы электрохимической регенерации ХПР. Разработаны варианты технологических схем для очистки природных и технологических газов от H2S с получением тонкодисперсной серы и возможностью комбинирования этих технологий с технологией полимерной серы, что повышает экономическую эффективность хингидронного процесса очистки газов. The dissertation presents the results of research aimed at the development of theoretical foundations and technologies for the purification of oxygen-free (natural and technological) gases from H2S by quinhydrone oxidizing systems (QOS). The resources and composition of hydrogen sulfide-containing gases that need purification and can be raw materials for the production of sulfur or its compounds have been monitored. It is shown that the current technologies of gas purification often do not provide complete purification of gases from H2S, its utilization, are complex, energyintensive, obsolete, and need improvement. The stages of the quinhydrone method of gas purification from H2S, which has experience in industrial applications, but only for the purification of ventilation (oxygen-containing) gases, are analyzed. It is shown that to adapt the method for purification of oxygen-free (natural and technological) gases, it is first necessary to take measures to reduce the negative impact of the oxidation reaction of chemisorbed H2S with O2, accompanied by Na2S2O3 formation, its accumulation, and subsequent processes of waste thiosulfates. The mutual solubility and physicochemical properties of the solution at high concentrations of ingredients in quinhydrone absorbing solution (QAS) were studied. On their basis, theoretical calculations were performed and the choice of mass transfer apparatus was substantiated, which most closely corresponds to the physicochemical bases of oxygen-free gas purification. For purification of gases under atmospheric pressure at the stages of chemisorption of H2S and O2, a horizontal absorber with bucket-shaped dispersants (HABD) is recommended, and for purification under pressure - bubble absorbers. The influence of the conditions of QOS formation on its redox and physicochemical properties has been studied. It is shown that the preparation of QAS based on QOC makes it possible to improve the technology of oxygen-free gases purification from H2S and obtain a given additional product. The phase equilibrium in the H2S - QAS system at different Na2CO3 concentrations was studied. It was found that the phase distribution coefficient mpx increases sharply with increasing saturation of the solution and decreases with increasing Na2CO3 concentration. The equilibrium constant of the H2S chemisorption reaction depends on the initial concentration of Na2CO3 and is equal to 0.1…0.35 mol/(m3.Pa). These data were used to develop a two-stage gas purification scheme. Using the criterion equations and the results of phase equilibrium studies, a mathematical model of H2S chemisorption from gases by QAS in the bubbling model was developed, which takes into account the influence of gas pressure and saturation of H2S solution at different Na2CO3 concentrations. The influence of various factors on the chemisorption of H2S from oxygen-free gases of QAS in bubbling and mechanical dispersing absorbers has been experimentally investigated. It is established that at low degrees of saturation of H2S solution in bubble absorbers the resistance of the system is determined by the resistance from the gas phase. The increase in pressure naturally contributes to the growth of the driving force of the chemisorption process of H2S by QAS. The rate of chemisorption increases with increasing pressure in proportion to Pn (n=0.82…0.83), which is characteristic of systems with "moderately soluble" gas, i.e. those that are limited by resistance from both gas and liquid phases. The value of the linear velocity of the disperser bucket ends (12 m/s) in the HABD was established, at which the resistance from the gas phase has a decisive influence on the kinetics of H2S chemisorption from oxygen-free gases. At the same time, the lowest resistance from the gas phase is achieved at the maximum gas velocities in the absorber 1.8...2.0 m/s. Using the criterion equations, the process of O2 chemisorption from QAS air at the stage of its regeneration in a vertical apparatus with a continuous bubbling layer (VABL) was calculated. The influence of various factors on this process in two types of absorbers - VABL and HABD is experimentally investigated. It is established that the rate of O2 chemisorption of QAS in VABL devices increases with increasing airflow. However, the rate of the chemical reaction between chemisorbed O2 and the reductive form of QOC is much higher (310…430 times) than the rate of O2 chemisorption. Therefore, this type of mass transfer equipment is not recommended for the regeneration of QAS by air oxygen. It is shown that the selective oxidation of chemisorbed H2S with the formation of fine sulfur during electrochemical regeneration of the absorption solution is achieved at low current densities (up to 15…17 A/dm2 ) and the process duration is up to 5 min. At higher densities, due to the increase in pH, by-products are formed (mainly Na2S2O3 and Na2SO4), which impair the sorption properties of QAS. During the electrochemical regeneration of QAS, competing processes of oxidation of chemisorbed H2S and reductive forms of QOC take place, which reduces the efficiency of solution regeneration. In the absence of sulfur compounds in QAS during electrochemical regeneration, the concentration of oxidative forms of QOS increases by 12…30%. It is shown that the decrease in the chemisorption degree of H S when using absorption solutions with a high concentration of Na2S2O3 (up to 350 kg/m3 ) can be compensated by a slight increase in temperature up to 303...308K. This will directly use waste solutions as raw materials for polymer sulfur obtaining. The pH limits (not higher than 8.8… 8.9) are set, at which fine sulfur is obtained with a high yield during gas purification. This is due to the relatively high concentration of NaHCO3 compared to Na2CO3 in the absorbing solution. Variants of technological schemes for purification of natural, associated, coke, pyrolysis, bio, and other gases with the production of fine sulfur and the possibility of combining these technologies with polymeric sulfur technology, which increases the economic efficiency of quinhydrone method gas desulfurization process.
Теоретические основы и технологии очистки бескислородных газов от сероводорода хингидронным методом
Theoretical basis and technologies of oxygen-free gases purification from hydrogen sulfide by quinhydrone method.
Keywords: природні гази; технологічні гази; сірководень; очищення; хемосорбція; поглинальний розчин; хінгідронні окисні системи; хімічна регенерація; кисень повітря; електрохімічна регенерація; дрібнодисперсна сірка; природные газы; технологические газы; сероводород; очистка; хемосорбция; поглотительный раствор; хингидронные окислительные системы; химическая регенерация; кислород воздуха; электрохимическая регенерация; тонкодисперсная сера; natural gases; process gases; hydrogen sulfide; purification; chemisorption; absorption solution; quinhydrone oxidizer systems; chemical regeneration; oxygen; electrochemical regeneration; fine sulfur; 66.074.5:661.214